Pendampingan Digital Marketing Sebagai Strategi Pemasaran UMKM Bawang Goreng Murni - Wildan Jovian Wahyu Tyas Saputra; R. Yuniadi Rusdianto (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Pure fried onion MSMEs are one of the businesses located in Tanjungsari Village, Sukorejo District, Blitar City. This MSME is engaged in food made from shallots. The difficulty of understanding how to use digital marketing causes Bawang Goreng Murni business to be limited to only doing word-of-mouth marketing. Therefore, there is a need for socialization and assistance regarding digital marketing and the benefits of this type of marketing for Pure Fried Onion MSMEs. The methods carried out in conducting this assistance are surveys, questionnaires, socialization, FGD, and direct practice to Pure Fried Onion MSMEs. The results of the research of Pure Fried Onion MSMEs can understand the importance of digital marketing. These MSMEs can also understand how to use digital marketing platforms that can be used to do marketing. Mentoring activities carried out for Pure Fried Onion MSMEs are expected to increase sales quantity and competitive ability in today's digital era.